Scarcity in the Land of Plenty - Jesse Madden Libra; Julien Sylvain Marinus Collaer; Darcia Datshkovsky; Maria Pérez-Urdiales (Inter-American Development Bank, 2022)
Latin America and the Caribbean (LAC) is the most water-rich region in the world, but millions of its inhabitants live with water risk. This contradiction, driven by mismatches in the location of supply vs demand, quality issues, and failing infrastructure, makes it crucial that policy makers use people-centric water risk metrics when assessing water risk in LAC. 35% of the population lives in water stressed basins, a number which balloons to 60% when accounting for the lack of institutional capacity for preserving water quality and providing water services.
Keywords: Q25; Q54; Q56; R11; 330; water stress; water scarcity; water risk; climate change; population - based metrics